Accelerating digitalisation in business practices for social value creation: Malaysia perspective / Nur Syuhada Jasni and Haslinda Yusoff - Jasni, Nur Syuhada; Yusoff, Haslinda (Faculty of Accountancy, 2019)
Today, digitalisation is rising aggressively in reaching people and changing their lives. Among telecommunication companies, they are competing in providing better digital service to win the market segmentation. The competition is consider healthy as it brings prosperous to the users and societies as a whole. Specifically, the digitalisation progress lead to an increase in socio-economy and offer significant social value-added benefits. Telecommunication companies in Malaysia are very fortunate, as government also give them full support to enhance digitalisation that contributing to social and economic development in this country. However, although the companies are in the same industry, the way they addressed the social issues are different, hence it is interesting to explore in deeper understanding the business approach taken by them. Furthermore, this study focuses on the social value creation accelerating digitalisation from corporate perspective in Malaysia context. In additional, this study provides the review of the relevant literature on social value creation concept. In this study, content analysis is used to extract the relevant information from the latest sustainability report of telecommunication companies in Malaysia. Besides, this study addressed six social issues from literatures; discover young talents in technology and digitalisation for new economy, empower women in technology and digitalisation, digital risks and threats including cyberbullying and online predators, remove distance as a barrier of technology and digitalisation and manage smart city system (IoT), and providing rural and urban poor communities’ digitalisation assistance. The findings highlight that companies show efforts in embracing the social value creation concept that supports aligned with national objectives and Sustainability Development Goals (SDGs). Among all social issues addressed, the sample shows that they have their similarity in addressing social issue, which is providing rural and urban poor communities’ digitalisation assistance. Consequently, this study also gives input on other social issues that need to improve in the future. In the future, a study should be conducted to investigate the financial implications of the social projects in line. It is hoped that the social projects and practices will be bring high impact to societies and country, meanwhile for companies itself function as sustainable business strategy in practice and reporting towards Integrated Reporting (IR) 4.0.